FURO/CAP: A protocol for sodium intake sensitization - Pereira, Daniela T. B. [UNESP]; Menani, José Vanderlei [UNESP]; De Luca, Laurival A. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
We investigated if a history of FURO/CAP, a protocol that increases brain angiotensin II (ANG II), sensitizes or enhances sodium intake. A subcutaneous injection of the diuretic furosemide (FURO, 10 mg/kg) was combined with a converting enzyme inhibitor captopril (CAP, 5 mg/kg) to induce a short latency stimulated sodium (0.3 M NaCl) and water intake in a 2 h FURO/CAP test. Repeated injections of only FURO/CAP, separated by one-week interval, enhanced stimulated and spontaneous (daily) sodium intake. Stimulated fluid intake was completely suppressed when FURO/CAP was combined with two intraperitoneal injections of the ANG II type-1 receptor antagonist losartan (10, 20, or 40 mg/kg each) given within 1 h prior to the FURO/CAP test. Losartan reduced by only 35% the FURO/CAP-induced natriuresis. A history of FURO/CAP, FURO/CAP + losartan (all doses), or vehicle produced similar stimulated fluid intake when all animals received only FURO/CAP in the third final FURO/CAP test. However, a history of vehicle or FURO/CAP + losartan 10 mg/kg precluded the enhancement in spontaneous sodium intake after the third final FURO/CAP. The FURO/CAP combined with losartan (all doses) also precluded the spontaneous sodium intake enhancement in the weeks that preceded the third final FURO/CAP test. A history of only FURO/CAP, but not vehicle, also enhanced water deprivation-induced sodium appetite. The results suggest that a history of FURO/CAP enhances stimulated and spontaneous sodium intake, as well as water deprivation-induced sodium appetite, and reinforce the role of ANG II as a peptide that mediates long-term effects on behavior. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Sodium appetite; Angiotensin; AT1 receptor; Losartan; Water deprivation; Enhancement; Natriuresis; Addiction